Maritime Cooperation Between Indonesia and South Korea: Analysis of MTCRC (Marine Technology Cooperation Research Centre) - Haris, Aisyiah Putri; Seniwati, (Technium Social Sciences Journal, 2024)
Indonesia is the largest archipelago with abundant marine resources. To manage this optimally, Indonesia needs to cooperate with other countries to optimise it. The main focus of this study is the Marine Technology Cooperation Research Centre (MTCRC), a collaborative marine science and technology research establishment managed by the Korea Institute of Ocean Science and Technology (KIOST) and the Bandung Institute of Technology (ITB) between both the governments of South Korea and Indonesia. This research aims to analyse the functioning of Indonesia’s maritime cooperation with South Korea. The data collection method through library research and the theory of international cooperation are used to analyse this research. This study's results show that the maritime technology collaboration between South Korea and Indonesia research centres has built and implemented programs to support marine science and technology cooperation.